Sol–gel synthesis of doped Cu2V2O7 fine particles showing giant negative thermal expansion - M. Sato; V. Warne-Lang; Y. Kadowaki; N. Katayama; Y. Okamoto; K. Takenaka (AIP Advances, 2020)
We report the sol–gel synthesis of Cu2V2O7 fine particles, in which some of the constituent Cu is replaced with other elements. The sintered body of Zn substituted β-Cu1.8Zn0.2V2O7 shows a large negative thermal expansion (NTE) over a wide temperature range due to microstructural effects peculiar to a ceramic body. Using the sol–gel method, we successfully produced β-Cu1.8Zn0.2V2O7 ceramic fine particles that retain the same level of thermal expansion suppression capabilities as the bulk with a size of about 1 μm. We also succeeded in performing rare earth metal (Ce, Sm, Yb) substitutions, which might be a clue for improving NTE performance. These achievements provide particulate filler for thermal expansion control of a micrometer region, which has been earnestly sought in many fields of technology.